Historical and health insights into wedang uwuh: a traditional Indonesian beverage - Athiefah Fauziyyah; Athila Safira Rahma; Dini Nur Hakiki; Qabul Dinanta Utama (Journal of Ethnic Foods)
Abstract Wedang uwuh is a traditional Indonesian beverage composed of various spices known for their bioactive compounds, which exhibit antioxidant, antimicrobial, and antidiabetic properties. Its distinctive flavor and health-promoting characteristics highlight its potential as a functional beverage. This article provides a comprehensive overview of wedang uwuh, including its historical background, preparation methods, bioactive components, and associated health benefits. It also discusses current developments and identifies key challenges in product innovation, such as packaging, sweetener alternatives, safety evaluation, and consumer acceptance. Addressing these challenges through targeted research and development is essential to support the successful commercialization of wedang uwuh while preserving its traditional values and functional integrity.